PELAKSANAAN PEMBELAJARAN BERDIFFERENSIASI DI KELAS INKLUSIF SEKOLAH DASAR ISLAM FATHIA SUKABUMI - Edih; Arsyi Rizqia Amalia; Astri Sutisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Differentiated instruction is a learning approach that adapts content, process, and learning products to students’ needs, abilities, and characteristics. This study aims to describe the implementation of differentiated instruction in inclusive classrooms at Fathia Islamic Elementary School, Sukabumi. This research employed a qualitative approach using a descriptive method. The research subjects included classroom teachers, special assistant teachers, and students in inclusive classrooms. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that differentiated instruction at Fathia Islamic Elementary School has been implemented through adjustments in learning strategies, the use of varied media and methods, and the provision of assignments tailored to students’ abilities, including students with special needs. However, several challenges remain, such as limited time, inadequate facilities, and teachers’ competencies in designing optimal differentiated instruction. This study is expected to contribute to the improvement of inclusive learning practices in elementary schools.